A partnership between researchers and breastfeeding advocates to support safe alcohol consumption during breastfeeding - Giglia, Roslyn (Australian Breastfeeding Association, 2016)
In 2009 the first national and international guideline providing direction for breastfeeding women on drinking alcohol was included in the National Health and Medical Research Council Australian guidelines to reduce health risks from drinking alcohol. In the absence of an accompanying education campaign for the guidelines, the Australian Breastfeeding Association was able to fill this gap and work in partnership with a breastfeeding researcher to develop an education resource for Australian women that was also a national and international first. This commentary outlines the journey of the research that informed the development of the resource and the integral involvement of the Australian Breastfeeding Association throughout.